Управління водними ресурсами в межах басейну річки Південний Буг на території Кіровоградської області - Годорожа, Артем Михайлович; Hodorozha, Artem (ЦНТУ, 2021)
Мета роботи - дослідження теоретичних основ, аналіз сутності, переваг та недоліків системи управління водними ресурсами за басейновим принципом, стан якості поверхневих вод басейну ріки Південний Буг. Висвітлено характеристику водних ресурсів України, їх екологічний стан, шляхи відновлення та оздоровлення малих річок. Досліджено річковий басейн річки Південний Буг на території Кіровоградської області. Визначено якість води масивів поверхневих вод. Запропоновано перспективні принципи впровадження басейнового принципу. He purpose of the work is to study the theoretical foundations, analyze the nature, advantages and disadvantages of the basin water management system, the state of surface water quality of the Southern Bug river basin. The characteristics of water resources of Ukraine, their ecological condition, ways of restoration and improvement of small rivers are covered. The river basin of the Southern Bug river in the Kirovohrad region has been studied. The water quality of surface water massifs is determined. Perspective principles of basin principle implementation are offered.
Water resources management within the Southern Bug river basin in the Kirovohrad region
Keywords: річковий басейн; водні ресурси; якість води; екологічний стан; басейновий принцип управління водними ресурсами; гідрохімічні показники; моніторинг довкілля; масиви поверхневих вод; питний водозабір; водний об’єкт; водозабезпеченість; river basin; water resources; water quality; ecological status; basin principle of water resources management; hydrochemical indicators; environmental monitoring; surface water massifs; drinking water intake; water body; water supply